Microbial Profiling of Dental Biofilms in Cavitated and Non-Cavitated Carious Lesions - Dr. P.R. SANJAYA M.D.S. (The Bioscan, 2025)
Dental caries remains one of the most prevalent chronic oral diseases worldwide, arising from complex interactions between host factors, diet, and microbial communities within dental biofilms. Recent advances in molecular microbiology have revealed that caries is not the outcome of a single pathogen, but rather the result of a dynamic shift in the balance of diverse microbial populations inhabiting the oral cavity. This study focuses on microbial profiling of biofilms associated with cavitated and non-cavitated carious lesions, aiming to delineate the distinct microbial signatures that contribute to the initiation and progression of caries. Clinical samples were collected from patients presenting with early non-cavitated white spot lesions as well as advanced cavitated dentinal caries. High-throughput sequencing techniques, complemented with culture-based assays, were employed to characterize the bacterial composition. Comparative analyses highlighted a clear microbial gradient from non-cavitated to cavitated lesions. Non-cavitated lesions were predominantly enriched with early colonizers such as Streptococcus sanguinis, Streptococcus gordonii, and Actinomyces spp., which are typically associated with initial plaque biofilm formation. These organisms contributed to biofilm stability but exhibited moderate acidogenic potential. In contrast, cavitated lesions demonstrated a significant dominance of acidogenic and aciduric species, including Streptococcus mutans, Lactobacillus spp., and Bifidobacterium dentium. The metabolic activities of these microorganisms, particularly their capacity for sustained acid production under low pH conditions, correlated strongly with demineralization and lesion advancement. Additionally, metagenomic profiling revealed a greater prevalence of anaerobic taxa such as Veillonella and Prevotella, suggesting a microbial shift towards a more complex, pathogenic community as cavitation progresses. Functional annotation of microbial genes further indicated enhanced carbohydrate metabolism and acid tolerance pathways in cavitated lesions compared with non-cavitated sites. The study underscores the significance of ecological succession within dental biofilms, illustrating how subtle microbial imbalances can transition a biofilm from a relatively stable state to a highly cariogenic consortium. These findings emphasize the need for preventive strategies targeting early microbial changes before cavitation occurs. Moreover, microbial profiling may serve as a diagnostic adjunct to identify high-risk patients and guide personalized caries management. By bridging clinical presentation with microbial ecology, this research contributes to a deeper understanding of caries pathogenesis and highlights novel avenues for preventive and therapeutic interventions.